A Synthetic Route to Quaternary Pyridinium Salt-Functionalized Silsesquioxanes. (25th September 2012) - Kostenko, Nataliya; Gottfriedsen, Jochen; Hilfert, Liane; Edelmann, Frank T.
Abstract : A synthetic route to potentially biocidal silsesquioxanes functionalized by quaternary pyridinium functionalities has been developed. N -Alkylation reactions of the precursor compounds 4-(2-(trimethoxysilyl)ethyl)-pyridine (5 ) and 4-(2-trichloro-silylethyl)pyridine (6 ) with iodomethane, n -hexylbromide, and n -hexadecylbromide cleanly afforded the corresponding N -alkylpyridinium salts (7 –10 ). The synthesis of a 4-(2-ethyl)pyridine POSS derivative (2 ) was achieved by capping of the silsesquioxane trisilanol Cy7 Si7 O9 (OH)3 (1 ) via two different preparative routes. Attempts to use compound2 as precursor for quaternary pyridinium salt-functionalized POSS derivatives were met with only partial success. Only the reaction with iodomethane cleanly afforded the new N -methylpyridinium salt12 in high yield, whereas n -hexylbromide and n -hexadecylbromide failed to react with2 even under forcing conditions.